Basking Shark (Cetorhinus maximus) Movements in the Eastern North Pacific Determined Using Satellite Telemetry - Dewar, Heidi; Wilson, Steven G.; Hyde, John R.; Snodgrass, Owyn E.; Leising, Andrew; Lam, Chi H.; Domokos, Réka; Wraith, James A.; Bograd, Steven J.; Van Sommeran, Sean R.; Kohin, Suzanne (Frontiers in Marine Science, 2018)
To fill data gaps on movements, behaviors and habitat use both near- and offshore, two programs were initiated to deploy satellite tags on basking sharks. Basking sharks are large filter feeding sharks that are second in size only to whale sharks. Similar to many megafauna populations, available data suggest that populations are below historic levels. In the northeast Pacific Ocean, the limited information on basking sharks comes from nearshore habitats where they forage. From 2010-2011, four sharks were tagged with pop-off satellite archival tags with deployments ranging from 9-240 days. The tags provided both transmitted and archived data on habitat use and geographic movement patterns. Nearshore, sharks tended to move north in the summer and prefer shelf and slope habitat around San Diego, Point Conception and Monterey Bay. The two sharks with 180 and 240 day deployments left the coast in the summer and fall. Offshore their paths diverged and by January one shark had moved to near the tip of the Baja Peninsula, Mexico and the other to the waters near Hawaii, USA. Vertical habitat use was variable both within and among individuals and changed as sharks moved offshore. Nearshore, most time was spent in the mixed layer but sharks did spend hours in cold waters below the mixed layer. Offshore vertical movements depended on location. The shark that went to Hawaii had a distinct diel pattern, with days spent at ~450-470 m and nights at ~250-300 m and almost no time in surface waters, corresponding with the diel migration of a specific portion of the deep scattering layer. The shark that moved south along the Baja Peninsula spent progressively more time in deep water but came to the surface daily. Movement patterns and shifts in vertical habitat and use are likely linked to shifts in prey availability. Data collected indicate the potential for large-scale movements and the need for international dialogue in any recovery efforts.